34. PREVALENCE OF COEXISTING COMMON NON-COMMUNICABLE DISEASES AMONG PEOPLE AGED 30-69 IN DA NANG CITY (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the prevalence of common non-communicable diseases and analyze associated factors among people aged 30-69 years in Da Nang city.Method: A cross-sectional descriptive study was conducted using 1788 representative samples collected in 2021 with the WHO STEPS tool. Data were analyzed using SPSS software with Chi-square tests and logistic regression to determine associations between multimorbidity and risk factors.Results: The prevalence of having ≥ 1 non-communicable diseases was 39.7%, and ≥ 2 non-communicable diseases (multimorbidity) was 10.2%. Common conditions included hypertension (28.3%), dyslipidemia (19.8%), obesity (18.4%), and diabetes (7.1%). Multimorbidity was more common among those aged ≥ 60, males, individuals with high BMI, smokers, physically inactive persons, and those with low vegetable intake. These associations were statistically significant (p < 0.05).Conclusion: Multimorbidity is notably present in the community. Behavioral interventions, screening, and integrated management at the primary healthcare level are essential.
Keywords: Non-communicable diseases; multimorbidity; hypertension; diabetes; risk factors.